THE INFLUENCE OF SOCIO-ECONOMIC FACTORS OF MOTIVATION ON LABOR PRODUCTIVITY IN THE EFFECTIVE AGRIBUSINESS SYSTEM - Alina Herasymenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The article examines the impact of labor productivity on the development of agriculture. It was established that labor productivity is the main lever for creating additional value and a source of economic growth of agricultural production. An assessment of the achieved level of labor productivity in the agriculture of Ukraine was carried out on the basis of economic and statistical analysis. The monitoring of wage dynamics as the main socioeconomic factor of increasing the productivity of agricultural labor was carried out. A comparative analysis of the rate of increase in labor productivity and the rate of growth of its payment was done. The obtained results made it possible to reveal the presence of disproportions in the agrarian sphere of Ukraine between these indicators. A comparative assessment of the level of labor productivity in domestic agriculture and EU countries proved that the rate of growth of agricultural labor productivity in Ukraine is significantly behind the average European indicators. A set of socio-economic motivators for increasing labor productivity in agricultural production is substantiated on the basis of the research results. It was established that remuneration systems for hired labor remain the main socioeconomic factor stimulating the growth of labor productivity in agrarian business. At the same time, a set of socio-economic motivators, which, in addition to wages, can be effective in stimulating the growth of agricultural labor productivity has been determined. Among the key motivators, the following ones are proposed for use in the modern HR policy of agrarian formations: opportunities for professional development of personnel, opportunities for employees to influence making important management decisions, increasing the prestige of agricultural work, appreciation and self-realization of workers. It was determined that the principles of sustainable development and the elimination of inclusive gaps in the industry should be an important prerequisite for increasing labor productivity in the agricultural economy of Ukraine.